(untitled) (Transactions of the Association of European Schools of Planning, 2018)
Starting in the 1990s, an increasing number of studies and reports have focused on examining the nature and characteristics of spatial planning in Europe. The geographical coverage of these comparative analyses broadened over time, paralleling the progression of EU integration. However, the Western Balkan countries were only vaguely mentioned within such studies, mostly due to their fragmentation and geopolitical instability. This paper analyses and compares spatial planning systems in the Western Balkan Region since the 1990s. More specifically, it presents an overview of the geographical and socio-economic situation, explores administrative and legal frameworks for spatial planning, analyses spatial planning instruments produced at each territorial level, and addresses future challenges. Through so doing this paper exposes the complexity of the subject and sets a base for further research.